2019
DOI: 10.3390/app9163344
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Virtual Sensor for Estimating Robot Joint Total Friction Based on Total Momentum

Abstract: Robot joint friction is an important and complicated issue in improving robot control performance. In this paper, a virtual sensor based on the total generalized momentum concept is proposed to estimate the total friction torque, including both the motor-side and link-side friction, of robot joints without joint torque sensors. The proposed algorithm only requires a robot joint dynamics model and not a complex friction model dependent on factors such as time and velocity. By compensating for the estimated fric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…erefore, it can be known that (e, _ e) � (0, 0) is the global asymptotically stable equilibrium point of the exoskeleton system from the LaSalle theorem. In addition, more similar robot controller stability analyses can also be found in [31,37,38].…”
Section: System Stability Analysismentioning
confidence: 99%
“…erefore, it can be known that (e, _ e) � (0, 0) is the global asymptotically stable equilibrium point of the exoskeleton system from the LaSalle theorem. In addition, more similar robot controller stability analyses can also be found in [31,37,38].…”
Section: System Stability Analysismentioning
confidence: 99%
“…With an increase in speed, the joint friction effect becomes significant [20,21], and friction effect plays an important role in controlling and tracking the accuracy of the parallel manipulator [22]. Unsworth's [23] experiments with artificial hip joint friction measurements using the Durham friction simulator showed that hip joint friction under high loads cannot be ignored.…”
Section: Introductionmentioning
confidence: 99%
“…This process is performed by rewriting the equations in matrix form and linear regression, using the least-squares method. Xu et al 5 showed the total friction in the system by one term in these equations and considered it a disturbance term, and designed a virtual sensor to observe its value by considering the dynamic equations of the system. For the obtained equation, a diagonal matrix was developed to determine its correct values, and subsequently to result in the precise friction value.…”
Section: Introductionmentioning
confidence: 99%